2023
DOI: 10.3390/cryst13030448
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional MoS2 Nanosheet Structures: CVD Synthesis, Characterization, and Electrical Properties

Abstract: The proposed study demonstrates a single-step CVD method for synthesizing three-dimensional vertical MoS2 nanosheets. The postulated synthesizing approach employs a temperature ramp with a continuous N2 gas flow during the deposition process. The distinctive signals of MoS2 were revealed via Raman spectroscopy study, and the substantial frequency difference in the characteristic signals supported the bulk nature of the synthesized material. Additionally, XRD measurements sustained the material’s crystallinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The FETs derived from individual flakes had a channel length (L) = and width (W) = , while those from the thin film had L = and W = , as shown in the SEM images of the Figure 3 a,b inset. For detailed information on the deposition and device processing parameters, please refer to the reported work of Mathew, S. et al [ 14 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FETs derived from individual flakes had a channel length (L) = and width (W) = , while those from the thin film had L = and W = , as shown in the SEM images of the Figure 3 a,b inset. For detailed information on the deposition and device processing parameters, please refer to the reported work of Mathew, S. et al [ 14 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FETs derived from individual flakes had a channel length (L) = 3.5 µm and width (W) = 15.5 µm, while those from the thin film had L = 13.5 µm and W = 50.4 µm, as shown in the SEM images of the Figure 3a,b inset. For detailed information on the deposition and device processing parameters, please refer to the reported work of Mathew, S. et al [14,24]. The Raman spectra obtained from the channel layer of the experimental back-gate FETs based on a MoS 2 flake and thin film are presented in Figure 3a,b, revealing two pronounced first-order Raman active modes of MoS 2 : E 1 2g and A 1g , corresponding to the in-plane vibration of the Mo-S bond along the base plane of the MoS 2 sheets, and the outof-plane vibration of S along the vertical plane of MoS 2 [4,[25][26][27].…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Linear structures that arise upon contact with crystallites growing along the substrate surface serve as centers for the formation of crystallites growing perpendicular to the substrate. The detailed mechanism of vertical structures protruding is still under discussion and requires additional investigations [52]. In general, however, when neighboring islands grow large enough so they come into contact, the atomic planes of these crystallites bend upward and expose their edges to precursorreach gaseous phases.…”
Section: (B)) At Earlier Stages (Corresponding To Larger Distances Be...mentioning
confidence: 99%
“…Chung et al [7], Xiong et al [11], Mathew et al [14], lee et al [15], Chen et al, [16] and Shen et al [17] reported NSFET based on TMD/MoS 2 with good performance metrics such as ON to OFF current ratio greater than 10 8 and high ON currents. However, these metrics are outside the range of predicted metrics as per the IRDS projections.…”
Section: Introductionmentioning
confidence: 99%